Prosecution of Felony Arrests, 1982: Portland, Oregon and Washington, D.C ([Verlag nicht ermittelbar], 1988)
This study provides statistical information on how prosecutors and the courts disposed of criminal cases involving adults arrested for felony crimes in two individual urban jurisdictions, Portland, Oregon and Washington, D.C. Cases in the data files were initiated or filed in 1982. Both the Washington, D.C. file and the Portland file contain information on all felony arrests (which include arrests declined as well as those filed), cases filed, and cases indicted. Sentencing information is provided in the Portland file but is not available for Washington D.C.